Prevention of HIV Transmission Among Men Who Have Sex with Men and Compliance with Sexual Protective Equipment - Sitorus, Rico Januar; Octavia, Nurafni; Panjaitan, Merry Natalia; Rahmiwati, Anita Rahmiwati; Syakurah, Rizma Adlia; Aerosta, Danny; Sangalang, Reymart V; Yusri, Yusri (UI Scholars Hub, 2024)
Sexual orientations, such as gay, lesbian, and bisexual, are prevalent among individuals at high risk of experiencing mental health problems, including drug use, depression, emotional distress, and suicide. Therefore, this study aimed to assess the compliance of men who have sex with men with protective equipment and determine the dominant influential factors. This cross-sectional study included 187 men who had sexual intercourse with men who were recruited from two foundations based in Palembang City, Indonesia, focusing on people living with HIV/AIDS. Data were analyzed using Chi-square and binomial logistic regression. In this context, 50.8% of men who have sexual intercourse with men did not comply with the use of sexual protective equipment, exceeding those in compliance. The multivariate logistic regression showed that knowledge was the dominant factor (PR = 15.733; 95% CI = 4.063-60.920), and most low-knowledge individuals were 15.733 times more at risk of non-compliance. Intensive education is needed regarding the potential risk of transmission, considering the ease of access to condoms.